Analyzing multiple household responses: Adoption of CSA practices - Muriel, Juliana; Twyman, Jennifer; Chavarro, Mónica Juliana (International Center for Tropical Agriculture, 2019)
Intra-household surveys permit us to recognize the individual preferences and perceptions of different household members. They also allow us to analyze gender gaps, bargaining power and empowerment. However, having multiple responses complicates household level analysis such as estimating agricultural yields and adoption rates. This infographic presents four ways of calculating household level adoption rates using two responses per household.